Contribution of Artists of Various Genres in the Promotion of Sufiyana Singing: Exploring the Influence of Artists in the Evolution and Dissemination of Sufi Music (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Music is a changing art, which from ancient times to modern times, in different forms ofmusic, along with human emotions, have been giving a feeling of joy. If seen from the historical point ofview, the arrival of Muslim culture to India in the 11th century had a profound effect on the culture, living,customs, food habits, literature, philosophy etc. The Muslim people could not understand the Indianlanguages, but they were greatly influenced by the scripts of Indian music, and the same influence wasseen in the music tradition of Punjab through Indian music. Different Sufi singers made their importantcontribution to carry forward the Sufi music tradition started by Sufi saints and mystics. There have beeninnumerable artists in the field of Sufi music, who propagated and disseminated Sufi music by reachingthe masses, including Mehfil-e-Samaa, Media, TV, which are held at the Dargahs of Sufi mystics.Channels, social media etc, played a major role as the medium of propagation of Sufi music.